Linguistic Analysis of English and Arabic Weather Proverbs - Hussein , Abbas Lutfi (International Journal of Psychosocial Rehabilitation, 2020)
Weather proverbs, folk sayings, are observed in every society to forecast atmospheric conditions. In English and Arabic, weather proverbs are presented as a collection of opinions, philosophies and thoughts of people towards climatic conditions. Yet, they are often uttered in fixed forms (words, expressions, phrases and sentences); that is, they enjoy miscellaneous linguistic (syntactic, lexical and semantic) characteristics and being realized in different senses when located in various settings. Thus, this paper intends to investigate the linguistic construction of weather proverbs in both English and Arabic languages. 180 English and Arabic weather proverbs (90 each) have been selected to qualitatively identify their syntactic, semantic and lexical features. The study concludes that both data nearly use the same linguistic resources to perform functions associated with weather state, with the exception some features related to language uniqueness.